Nationwide in-hospital mortality following colonic cancer resection according to hospital volume in Germany - Diers, Johannes; Wagner, J; Baum, Philip; Lichthardt, Sven; Kastner, Carolin; Matthes, N; Löb, S; Matthes, Harald; Germer, Christoph-Thomas; Wiegering, Armin (BJS open, 2019)
Colonic cancer is the most common cancer of the gastrointestinal tract. The aim of this study was to determine mortality rates following colonic cancer resection and the effect of hospital caseload on in-hospital mortality in Germany.Patients admitted with a diagnosis of colonic cancer undergoing colonic resection from 2012 to 2015 were identified from a nationwide registry using procedure codes. The outcome measure was in-hospital mortality. Hospitals were ranked according to their caseload for colonic cancer resection, and patients were categorized into five subgroups on the basis of hospital volume.Some 129 196 colonic cancer resections were reviewed. The overall in-house mortality rate was 5·8 per cent, ranging from 6·9 per cent (1775 of 25 657 patients) in very low-volume hospitals to 4·8 per cent (1239 of 25 825) in very high-volume centres (P < 0·001). In multivariable logistic regression analysis the risk-adjusted odds ratio for in-house mortality was 0·75 (95 per cent c.i. 0·66 to 0·84) in very high-volume hospitals performing a mean of 85·0 interventions per year, compared with that in very low-volume hospitals performing a mean of only 12·7 interventions annually, after adjustment for sex, age, co-morbidity, emergency procedures, prolonged mechanical ventilation and transfusion.In Germany, patients undergoing colonic cancer resections in high-volume hospitals had with improved outcomes compared with patients treated in low-volume hospitals.
Gesehen am 16.02.2022